DETERMINASI WHISTLEBLOWING INTENTION MELALUI SIKAP ETHICAL AWARENESS DAN ETHICAL JUDGEMENT - Ahmad Subaki; Sumarso Sumarso; Toto Tohari; Fikri Hidayat (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
Financial violations that occurred in Indonesia show no signs of ending soon. In the KPK report in 2022, there were 4,623 reports of alleged corruption through email and the KPK whistleblower system. This research was conducted empirically to reveal whether ethical awareness and ethical judgment affect a person's intention to whistleblow. The method used in this study is quantitative research method. Data collection is carried out in this using non-probability sampling or voluntary sampling techniques. Because in this study researchers collected data by distributing research questionnaires online through google form. The population in this study is FEB UHAMKA students who have obtained business law lessons. The number of samples obtained in this study was 249 respondents, this number of samples is above the minimum number of samples previously obtained using G-Power software. Then researchers use structural equation models with partial least square techniques through smartpls 4.0 software. The results of this study show that ethical awareness has a positive effect on the intention to whistleblow. Likewise with the variable of ethical judgment, it has a positive effect on the intention to do whistleblowing. Keywords: Ethical Awareness, Ethical Judgement, Whistleblowing